The major and the minor [videorecording (DVD)] - Brackett, Charles, 1892-1969; Wilder, Billy, 1906-2002; Rogers, Ginger, 1911-1995; Milland, Ray; Johnson, Rita, 1912-1965; Benchley, Robert, 1889-1945; Lynn, Diana (Universal Studios Home Entertainment, 2008)
A frustrated city girl decides to disguise herself as a youngster in order to get a cheaper train ticket home. But little "Sue Sue" finds herself in a whole heap of grown-up trouble when she hides out in a compartment with handsome Major Kirby and he insists on taking her to his military academy after the train is stalled.